Thoracic Endovascular Aortic Repair of Aortic Arch Pathologies with the Conformable Thoracic Aortic Graft: Early and 2 year Results from a European Multicentre Registry. Issue 6 (June 2016) - Böckler, D.; Brunkwall, J.; Taylor, P.R.; Mangialardi, N.; Hüsing, J.; Larzon, T.; ,
Abstract : Objective: To assess safety, effectiveness and clinical outcome of the conformable thoracic aortic endograft (CTAG) in the treatment of aortic arch pathologies. Methods: Between October 2009 and December 2010, 100 consecutive patients (65 men; mean age 65 years) with aortic arch pathologies were treated with the CTAG device in five European centres. Indications were thoracic aortic aneurysm ( n = 57), Type B dissection ( n = 24), intramural haematoma ( n = 4), penetrating aortic ulcer ( n = 9), and traumatic transection ( n = 6). Emergency procedures were performed in 33%. The proximal landing zone (LZ) was LZ 0 in 7%, LZ 1 in14%, LZ 2 in 43%, and LZ 3 in 36%. Data were collected prospectively and analysed for technical and clinical success. Conformability and deployment accuracy were analysed on intra-operative angiography and post-operative computed tomography. Mean follow up was 24 ± 19 months (range, 0.3–36 months). Results: The 30 day, 1 and 2 year survival rates were 90%, 81%, and 74% respectively. The 2 year survival was 80% in the elective and 62% in the emergency groups ( p = .20). The major 30 day complication rate was 34%: primary Type Ia endoleak affected 1%, retrograde dissection in 1%, and the paraplegia and stroke rates at 30 days were 4% and 11%. Age > 70 years was an independent predictor for mortality and complications. The primary technical success rate was 92%; device deployment was successful in 100% and accurate in 99%. Conformability to the aortic arch was achieved in 95%. Conclusion: The CTAG stent graft shows high deployment accuracy, good conformability, and clinical effectiveness in the treatment of aortic arch pathologies. However, thoracic endovascular aortic repair in the arch is associated with a relatively high stroke rate. Further studies with more patients and longer follow up are needed to evaluate the long-term results.